KOAGULASI FLOKULASI UNTUK MENURUNKAN WARNA DENGAN KOAGULAN PAC PADA EFLUEN PENGOLAHAN LIMBAH PENCELUPAN BENANG - Enny Susanti (Purifikasi, 2003)
Pursuant to analysis efluen of textile wastewater treatment plant, still contain high of color in the effluent. This research using Polyaluminium chloride (PAC) and lime to remove the color in a batch or continuous mode. A jar test was used for the batch while sedimentation vessels were for the continuous experiment. From research result obtained that PAC can remove the colour efluen aboat 73,51 % and with the kaolin addition can remove 78,92 % of the color.